2021
DOI: 10.1177/10775587211030376
|View full text |Cite
|
Sign up to set email alerts
|

How Patient-Centered Medical Homes Integrate Dental Services Into Primary Care: A Scoping Review

Abstract: Integrated care delivery is at the core of patient-centered medical homes (PCMHs). The extent of integration of dental services in PCMHs for adults is largely unknown. We first identified dental–medical integrating processes from the literature and then conducted a scoping review using PRISMA guidelines to evaluate their implementation among PCMHs. Processes were categorized into workforce, information-sharing, evidence-based care, and measuring and monitoring. After screening, 16 articles describing 21 PCMHs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Moreover, PCMH models that have attempted oral health integration typically focus on children or adult subgroups such as pregnant women or individuals with diabetes. Using criteria modeled after behavioral health integration efforts, the authors found limited medical-dental integration efforts for adults (Gupta et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PCMH models that have attempted oral health integration typically focus on children or adult subgroups such as pregnant women or individuals with diabetes. Using criteria modeled after behavioral health integration efforts, the authors found limited medical-dental integration efforts for adults (Gupta et al 2022).…”
Section: Introductionmentioning
confidence: 99%